2022
DOI: 10.3389/fped.2021.801955
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Mortality From Late-Onset Sepsis Among Preterm Very-Low-Birthweight Infants: A Single-Center Cohort Study From Singapore

Abstract: ObjectiveTo determine the risk factors for mortality associated with late onset sepsis (LOS) among preterm very-low-birthweight (VLBW) infants.Study DesignWe performed a retrospective cohort study of infants born <32 weeks gestation and <1,500 gm admitted to a Singaporean tertiary-level neonatal intensive care unit. We determined the clinical, microbial, and laboratory risk factors associated with mortality due to culture-positive LOS in this cohort.ResultsA total of 1,740 infants were admitted, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 54 publications
3
8
0
Order By: Relevance
“…Our results confirm the findings in a previous study of VLBW infants that multiple biomarkers can discriminate between GN sepsis and GP sepsis at the time of positive blood culture (12). Since Gram-negative infections and NEC are known to carry higher morbidity and mortality, this finding might be a useful adjunct clinical decision support tool in helping pick the appropriate empiric antibiotic therapy and institute treatment early (30)(31)(32). The current study adds to our prior work (12) because we analyzed samples remote from suspected sepsis.…”
Section: Discussionsupporting
confidence: 89%
“…Our results confirm the findings in a previous study of VLBW infants that multiple biomarkers can discriminate between GN sepsis and GP sepsis at the time of positive blood culture (12). Since Gram-negative infections and NEC are known to carry higher morbidity and mortality, this finding might be a useful adjunct clinical decision support tool in helping pick the appropriate empiric antibiotic therapy and institute treatment early (30)(31)(32). The current study adds to our prior work (12) because we analyzed samples remote from suspected sepsis.…”
Section: Discussionsupporting
confidence: 89%
“…Recently, the requirement for inotropic support was assessed to predict the mortality rate in newborns with sepsis. In a study population similar to ours, weighing under 1500 g and born before 32 weeks of gestation, the mortality risk was shown to be 22 times higher in a group of newborns requiring inotropic support [ 29 ]. The pooled OR for the need for vasoactive agents obtained from 20 studies analyzed in a recently published meta-analysis was 6.5 [ 23 ].…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, in our study, E. coli was the leading pathogen (29.2%) in regional general hospital, and the proportion was significantly higher than in national general hospital and maternal and child health care hospital. Other studies showed that the prevalence of Gram-negative bacteria was associated with high mortality ( 47 49 ). The proportion of complications and comorbidities, especially pneumonia and meningitis, were higher in regional general hospital, which might independently lead to sepsis-attributable mortality ( 50 , 51 ).…”
Section: Discussionmentioning
confidence: 99%